Reassessing the optimal volume for malignancy detection in serous fluid cytology. Issue 7 (25th April 2022) - Coconubo, Daniel Martínez; Baskota, Swikrity Upadhyay; Li, Runjia; Srivastava, Pooja; Cuda, Jackie; Khader, Samer
Abstract : BACKGROUND: The international system for reporting serous fluid cytopathology (TIS) recommends submitting at least 50‐75 mL of serous fluid to decrease false‐negative results. However, prior studies did not agree on specific volume requirements or consensus adequacy criteria. Our study aims to assess whether fluid volume affects the adequacy rate and to assess the minimum volume necessary for optimal adequacy in pleural and peritoneal fluids. METHODS: A total of 8530 serous fluid cytology cases were identified in the laboratory information system. Differences in mean fluid volume received in the laboratory were compared using an ANOVA Games‐Howell test based on TIS category. The percentage of malignant diagnoses across the volume ranges of 0 to 5 mL, 5 to 10 mL, 10 to 25 mL, 25 to 50 mL, 50 to 75 mL, 75 to 100 mL, 100 to 150 mL, 150 to 250 mL, 250 to 500 mL, 500 to 2000 mL was compared in pleural and peritoneal fluids using a chi‐square test, and a SiZer analysis was performed. RESULTS: Mean fluid volume in inadequate, atypical, and negative cases was significantly lower compared to positive cases. A SiZer analysis showed a positive relationship between the malignancy fraction of pleural and peritoneal fluids and fluid volume. The percentage of malignant diagnoses in pleural and peritoneal fluid samples increased significantly up to a volume range of 75‐100 mL. CONCLUSIONS: There is a significant relationship between fluid volume, adequacy and detection of malignancy in serous effusion cytopathology. The malignancy fraction increases with larger fluid volumes but at least 75‐100 mL of fluid should be submitted for optimal diagnosis of malignancy in pleural and peritoneal fluids.;